AI and historical disciplines in higher education: observations and perspectives - Kovalets, Taras (My University, 2023)
Kovalets T. AI and historical disciplines in higher education: observations and perspectives [в:] II Міжнародна науково-практична конференція «Молодіжна наука заради миру та розвитку», присвячена Всесвітньому дню науки 8–10 листопада 2023 року: Зб. матеріалів. Чернівці, 2023. С. 112-113.